The role of HIF-1α and VGSCs in influencing metastasis of breast cancer cells - Dewadas, Hemaniswarri Dewi (2018)
The role of HIF-1α as well as CBP and p300 in the regulation of VGSCs particularly the isoforms Nav1.5 and nNav1.5 which are highly expressed in aggressive breast cancer cells has yet to be explored. This study was designed to investigate the role of HIF-1α/CBP/p300 in the regulation of Nav1.5 and nNav1.5 in aggressive breast cancer. In doing so, this study was separated into three major chapters. The 1st Chapter: Characterisation of Nav1.5, nNav1.5, HIF-1α, and HIF-1α target gene, CA9 expressions in human breast cancer cell lines with different metastatic potential; the non-cancerous breast epithelial cell line (MCF-10A), the weakly metastatic breast cancer cell line (MCF-7), and the aggressive breast cancer cell line (MDA-MB-231). HIF-1α mRNA was detected in all three cell lines in which when normalised to MCF-10A, the highest expression was detected in MDA-MB-231 cells (4.6-fold, P ≤ 0.05), followed by MCF-7 cells (1.6-fold). Consistently, CA9 mRNA expression was detected at a higher level in MDA-MB-231 cells (12.9-fold, P ≤ 0.05) normalized to MCF-7 cells. Finally, expression level of Nav1.5 and nNav1.5 were also greater in MDA-MB-231 compared to MCF-7 cells (109.5-fold, P ≤ 0.01 and 120.4-fold, P ≤ 0.01 respectively). The 2nd Chapter: Elucidating the role of HIF-1α in regulating Nav1.5 and nNav1.5 expression and VGSC-mediated breast cancer metastasis. Using TRANSFAC and JASPAR2018, 3 possible binding sites for HIF-1α in the promoter region of Nav1.5 was revealed. HIF-1α knock-downed was achieved after 24 hr treatment with siRNA; HIF-1α mRNA and protein expression was down- regulated by 86.3% and 33%, respectively. The knock-downed was confirmed with down-regulation of CA9 mRNA expression level by 74.7%, P ≤ 0.01. siRNA-HIF-1α treated cells also showed significant decrease (by 31%, P ≤ 0.0001) in migration. CoCl2 (100 μM, 150 μM and 200 μM) successfully increased HIF-1α protein (up to > 600%) and mRNA expression of CA9 (up to 6 – 11-fold, P ≤ 0.05). This was followed by increased Nav1.5 mRNA expression (up to >1.3-1.6-fold). When growth of MCF-7 cells was not altered with CoCl2, motility and migration remain intact. The 3rd Chapter: Investigating the transcriptional regulation of Nav1.5 and nNav1.5 by HIF-1α and its co-activators, CBP and p300. mRNA expression levels of CBP and p300 were detected at higher level in MDA-MB-231 compared to MCF-7 cells. HIF-1α knocked-down significantly reduced the mRNA of CBP by 0.5-fold (P ≤ 0.05) in MDA-MB-231 cells whilst stabilisation of HIF-1α using CoCl2 caused a significant increase in the mRNA expression level of p300 by 1.2-fold (P ≤ 0.001). Treatment with C646 led to significant reduction in CBP and p300 mRNA (P ≤ 0.01). Similarly, CA9, Nav1.5 and nNav1.5 mRNA expression level in MDA-MB-231 cells was also down-regulated by C646 (up 60%, 50% and 30%, respectively, P ≤ 0.05). Finally, reduced metastatic abilities; motility and migration (up to 60% and 53%, respectively, P ≤ 0.001) were observed in MDA-MB-231 cells treated with C646. As a conclusion, HIF-1α/CBP/p300 altogether regulates the expression of Nav1.5 in breast cancer; interruption of HIF-1α/CBP/p300 lead to metastasis suppression in breast cancer cells. As for nNav1.5, current findings indicate that CBP/p300 able to the regulate nNav1.5, although its regulation by HIF-1α/CBP/p300 is yet to be re-evaluated. Nevertheless, targeting HIF-1α/CBP/p300/Nav1.5 could still be useful as potential strategy to combat Nav1.5-mediated breast cancer metastasis.